Peran Perempuan sebagai Buruh Harian Lepas Angkat Barang dalam Pemenuhan Kebutuhan Keluarga - Br Bangun, Lusia Nadia; Indrayani, Luh (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study explores the role of women as freelance porters in fulfilling family needs at Pasar Anyar, Buleleng. Women's involvement in the informal sector is a response to economic pressures within the household and limited access to formal employment opportunities. This research aims to describe the forms of women's participation as daily laborers, identify the social, economic, and cultural factors influencing their decision to work, and evaluate the impact of such work on family welfare. This study uses a descriptive qualitative method with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that women undertake dual roles as housewives and income earners due to low household income, the need to finance children's education, and economic hardship. Despite the physically demanding nature of the job and lack of legal protection, they continue to work to sustain their family's livelihood.